1993
DOI: 10.1002/eji.1830230754
|View full text |Cite
|
Sign up to set email alerts
|

In vivo enhancement of the specific antibody response via the low‐affinity receptor for IgE

Abstract: The ability of antigen-specific IgE antibodies to modulate the in vivo antibody response was studied by comparing the antibody response in mice immunized with 2,4,6-trinitrophenyl (TNP)-specific monoclonal IgE followed by bovine serum albumin (BSA)-TNP or with BSA-TNP alone. The serum IgG antibody response against BSA, measured in enzyme-linked immunosorbent assay ELISA, was enhanced up to 100-fold in groups receiving IgE. The enhancement required specific interaction between IgE and antigen, since no effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 26 publications
1
96
0
Order By: Relevance
“…First, not only MZ B cells (50), but also FO B cells, are able to present Ag. Second, although the majority of the Ag-presenting B cells would be unspecific (because they capture Ag via CD23 and not via the B cell receptor), the ensuing enhanced Ab response is strictly Ag specific (14,15), demonstrating that cognate interactions between CD4 ϩ T cells and B cells are required also in this situation. The biological role of IgE-mediated enhancement of immune responses is enigmatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, not only MZ B cells (50), but also FO B cells, are able to present Ag. Second, although the majority of the Ag-presenting B cells would be unspecific (because they capture Ag via CD23 and not via the B cell receptor), the ensuing enhanced Ab response is strictly Ag specific (14,15), demonstrating that cognate interactions between CD4 ϩ T cells and B cells are required also in this situation. The biological role of IgE-mediated enhancement of immune responses is enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced Ab response takes place in the absence of adjuvants and is constrained to antigenic determinants within the Ab-Ag complex (14,15). IgE administered with Ag enhances the production of specific primary IgG1, IgG2a, IgM, as well as IgE (15,17) and also induces a more efficient immunological memory than Ag alone (15).…”
mentioning
confidence: 99%
“…CD23 could enhance IgE antigen complex presentation 100-fold more than either unfocused or IgG bound antigen in animal studies. [25][26][27] The proposed roles for CD23 in antigen presentation include the binding of antigen-IgE-antibody complexes, internalization of the complexes, transport to compartments of the endosomal network containing proteolytic enzymes, interaction with major histocompatibility complex (MHC) class II antigens and interaction with CD21 at the points of contact on the Band T-cell surfaces. 28,29 An integrated CD23 is believed to be important for the IgE-mediated antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of IgE-induced antibody responses have exclusively measured serum responses [4,5,18,21]. To investigate the single B-cell response after immunization with IgE and antigen, ELISPOT assays were performed in parallel to ELISA.…”
Section: Ige Up-regulates the Number Of Specific B Cells In Spleenmentioning
confidence: 99%
“…The most recently discovered member of the family of 'enhancing isotypes' is IgE. In 1993 it was shown that mice given TNP-specific IgE before immunization with BSA-TNP produced up to 100-fold more BSA-specific antibodies than mice given antigen alone [4]. The enhancement affected specific IgG1-, IgG2a-, IgM-as well as IgE production, was dependent on T cells, and induced immunological memory [5].…”
Section: Introductionmentioning
confidence: 99%